Al-Zakat and its Role in Social Solidarit -The Zakat Fund in The Endowments of Samarra as a Model- - Bediwi , Salam (Islamic Sciences Journal, 2023)
Praise be to Allah, Lord of the Worlds, and blessings and peace be upon the latest of the Prophets and Messengers, and upon all his family and companions ... and after: One of the natural characteristics of humankind is that it is diverse in shapes, colors, and accidents, and that is why societies consist of various classes. Some of them are rich, some of them are poor, some of them are satisfied, and some of them are needy. Actions and conducts that make society fit for a decent life, including that it approved the assumption of zakat, made it the third pillar of Islam, and added charities to spread benefit and spread love and intimacy through social solidarity among members of society. Therefore, we shed light on one of those blessed doors in reality (the Zakat Fund in the Sunni Endowment Directorate in Samarra) to explain its details and how it works to achieve the desired goal by achieving social solidarity among the people of Samarra and its suburbs.